2016
DOI: 10.1190/tle35060490.1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent wave velocities in sediments and sedimentary rocks: Laboratory measurements and evidences

Abstract: The pioneering work of Mike Batzle and his colleagues has provided a fundamental understanding of mechanisms behind dispersion and attenuation of elastic waves in fluid-saturated rocks. It also has made way for a realization that these phenomena need to be accounted for in a better way when interpreting seismic and sonic data from the field. Laboratory experiments have formed the basis for new insight in the past and will continue to do so. Here, examples of experimental observations that give direct or indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Bauer et al . () demonstrated that the method yields result in good agreement with low‐frequency measurements of dynamic Young's modulus.…”
Section: Applicationsmentioning
confidence: 70%
See 2 more Smart Citations
“…Bauer et al . () demonstrated that the method yields result in good agreement with low‐frequency measurements of dynamic Young's modulus.…”
Section: Applicationsmentioning
confidence: 70%
“…It is well established that dynamic stiffness may depend on frequency, in particular in shales (Spencer ; Duranti, Ewy and Hofmann ; Batzle, Han and Hofmann ; Bauer et al . ). This phenomenon is called dispersion.…”
Section: Strain Ratementioning
confidence: 97%
See 1 more Smart Citation
“…To conclude this section, we point out that the classical Gassmann's theory suggests that the shear modulus of porous rock does not depend on the fluid saturation, while published laboratory data suggest that this conclusion is not always correct at low frequencies and for isotropic rock (e.g., Adam et al, ; Adam et al, ; Adam & Otheim, ; Bauer et al, ; Fabricius et al, ; Khazanehdari & Sothcott, ; Mikhaltsevitch et al, ). Consideration of the fluid effect on the shear modulus is outside of the scope of this paper.…”
Section: Gassmann's Theorymentioning
confidence: 94%
“…From a more general perspective, in spite of the very low permeability characteristics, shales are heterogeneous porous rocks, more or less containing elastic heterogeneities. Frequency‐dependent elastic behaviors of shales based on the laboratory measurements have been reported by Jones and Wang (), Duranti et al (), Hofmann (), Batzle et al (), and Bauer et al (). Therefore, shales should also be considered as naturally dispersive geomaterials, even their characteristic frequency might occur at very low frequency range since it takes extremely long time to achieve pore pressure equilibration (Batzle et al, ).…”
Section: Mobility Effect On Poroelastic Seismic Reflectivitymentioning
confidence: 99%